2021
DOI: 10.4149/bll_2021_115
|View full text |Cite
|
Sign up to set email alerts
|

Simple ultrasound evaluation of fetal adrenal glands as a marker of imminent preterm birth: a preliminary report

Abstract: OBJECTIVE: We present a simple 2D big ultrasound measurement of the fetal adrenal glands and their biometrical growth analysis highlighted as a potential preterm birth marker. METHODS: This was a prospective observational case-control study. Sixty-four patients were included in the study (32 with the diagnosis of imminent preterm birth before 37 and 32 controls) from January 2018 to May 2020. Anteroposterior dimensions and circumferences of the whole adrenal glands and their central zones were measured by simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…While three studies have previously demonstrated either whole gland or fetal zone enlargement, the use of clinically unavailable techniques, or need for highly experienced sonographers, are likely to have hindered clinical translatability. 10,23,24 To our knowledge, two previous studies have attempted to assess the normal fetal adrenal gland on MRI: one used single coronal images to determine a length and thickness to the gland 11 there was no consistency in slice used and it is unclear which measurements of the adrenal are most affected by volumetric change rendering this less relevant. Assessment of whole volumes is likely be more applicable to clincial practice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While three studies have previously demonstrated either whole gland or fetal zone enlargement, the use of clinically unavailable techniques, or need for highly experienced sonographers, are likely to have hindered clinical translatability. 10,23,24 To our knowledge, two previous studies have attempted to assess the normal fetal adrenal gland on MRI: one used single coronal images to determine a length and thickness to the gland 11 there was no consistency in slice used and it is unclear which measurements of the adrenal are most affected by volumetric change rendering this less relevant. Assessment of whole volumes is likely be more applicable to clincial practice.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, ultrasound assessment of the fetal adrenal for the prediction of preterm birth in high risk patients has been attempted. While three studies have previously demonstrated either whole gland or fetal zone enlargement, the use of clinically unavailable techniques, or need for highly experienced sonographers, are likely to have hindered clinical translatability 10,23,24 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations